Pharmacokinetic Study of Rucaparib in Patients With Advanced Solid Tumors. Issue 1 (25th May 2018) - Shapiro, Geoffrey I.; Kristeleit, Rebecca S.; Burris, Howard A.; LoRusso, Patricia; Patel, Manish R.; Drew, Yvette; Giordano, Heidi; Maloney, Lara; Watkins, Simon; Goble, Sandra; Jaw‐Tsai, Sarah; Xiao, Jim J.
Abstract: The phase 1‐2 study CO‐338‐010 (Study 10; NCT01482715) is evaluating single‐agent rucaparib, a poly(ADP‐ribose) polymerase inhibitor, administered orally to patients with an advanced solid tumor. In the dose escalation phase (Part 1), we characterized the single‐dose and steady‐state pharmacokinetic profiles of rucaparib administered once daily (QD; dose range, 40‐500 mg; n = 16) or twice daily (BID; dose range, 240‐840 mg; n = 30). Across all dosing schedules examined, the plasma exposure of rucaparib was approximately dose proportional; half‐life was approximately 17 hours, and median time to maximum concentration (tmax ) ranged from 1.5 to 6.0 hours after a single dose and 1.5 to 4.0 hours following repeated dosing. The steady‐state accumulation ratio ranged from 1.60 to 2.33 following QD dosing and 1.47 to 5.44 following BID dosing. No effect of food on rucaparib pharmacokinetics was observed with a single dose of 40 mg (n = 3) or 300 mg (n = 6). In a phase 2 portion of the study (Part 3), the pharmacokinetic profile of rucaparib was further evaluated at the recommended phase 2 dose of 600 mg BID (n = 26). The mean (coefficient of variation) steady‐state maximum concentration (Cmax ) and area under the concentration‐time curve from time zero to 12 hours (AUC0‐12h ) were 1940 ng/mL (54%) and 16 900 ng ⋅ h/mL (54%), respectively. A high‐fat meal moderately increased rucaparib exposure. The fed‐to‐fasted geometric mean ratios (90% confidence interval [CI]) for AUC0‐24h and Cmax were 138% (117%‐162%) and 120% (99.1%‐146%); the median (90%CI) tmax delay was 2.5 (0.5‐4.4) hours.